A discourse analysis of Malaysian university rankings in a local newspaper / Sean Harley Lee Allen - Sean, Harley Lee Allen (2014)
Education is indicated as a Malaysian Government priority based on extensive development of academic infrastructure. Incorporating internationalization is a primary goal through benchmarking against leading institutions worldwide. Ranking popularity has increased, influences national policies, shapes institutional identity, and directs academic decisions (Hazelkorn, 2009; Marginson and van der Wende, 2007; Holmes, 2006). Utilizing a discourse analysis approach suggested by Brown and Yule (1983) and Yule (2006), this study examines 40 newspaper articles from the New Straits Times involving ranking over seven years from 2004 until 2010. Little past research has been conducted involving text analysis within and above the sentence structure of printed newspapers to investigate how continued emphasis of the significance of ranking appeared to be maintained throughout a corpus. In addition to identified linguistic realizations, intertextuality and communicative purposes are explored to provide some contextual analytical reference. Recognizing organizational structures of a discourse enables more effective means of understanding involved subject matter through access to greater comprehensive depths of the relevant issue.